Modular Design of Highly Stable Semiconducting Porous Coordination Polymer for Efficient Electrosynthesis of Ammonia - Xue, Ziqian; Yao, Ming‐Shui; Otake, Ken‐ichi; Nishiyama, Yusuke; Aoyama, Yoshitaka; Zheng, Jia‐Jia; Zhang, Siquan; Kajiwara, Takashi; Horike, Satoshi; Kitagawa, Susumu (Angewandte Chemie International Edition, 2024)
Developing highly stable porous coordination polymers (PCPs) with integrated electrical conductivity is crucial for advancing our understanding of electrocatalytic mechanisms and the structure–activity relationship of electrocatalysts. However, achieving this goal remains a formidable challenge because of the electrochemical instability observed in most PCPs. Herein, we develop a “modular design” strategy to construct electrochemically stable semiconducting PCP, namely, Fe‐pyNDI, which incorporates a chain‐type Fe‐pyrazole metal cluster and π‐stacking column with effective synergistic effects. The three‐dimensional electron diffraction (3D ED) technique resolves the precise structure. Both theoretical and experimental investigation confirms that the π‐stacking column in Fe‐pyNDI can provide an efficient electron transport path and enhance the structural stability of the material. As a result, Fe‐pyNDI can serve as an efficient model electrocatalyst for nitrate reduction reaction (NO3RR) to ammonia with a superior ammonia yield of 339.2 μmol h−1 cm−2 (14677 μg h−1 mgcat.−1) and a faradaic efficiency of 87 % at neutral electrolyte, which is comparable to state‐of‐the‐art electrocatalysts. The in‐situ X‐ray absorption spectroscopy (XAS) reveals that during the reaction, the structure of Fe‐pyNDI can be kept, while part of the Fe3+ in Fe‐pyNDI was reduced in situ to Fe2+, which serves as the potential active species for NO3RR. A semiconductive PCP with excellent chemical and thermal stability was constructed using the “modular design” approach. The Fe‐pyNDI exhibits a well‐defined structure and shows promise as a new platform for investigating electrocatalysts for superior catalytic performance in reducing nitrate to ammonia. In‐situ X‐ray absorption spectra analysis during the reaction revealed that some of the Fe3+ present in Fe‐pyNDI underwent reduction to Fe2+, which serves as a potential active species for the nitrate reduction reaction.